Au croisement des mondialisations. Le cas du chanteur Sami Yusuf - Farid El Asri (Recherches sociologiques et anthropologiques, 2006)
During the last decennium Muslim artists have emerged in Europe who without renouncing their religion makes for more freedom. Singers, for instance, availing themselves of instruments of dubious orthodoxy, have contributed to the cultural globalization now afoot. These stars are applauded beyond the frontiers of the Old World and their careers are followed eagerly in the Muslim world – Sami Yusuf being typical. Living in London he has combined traditional Nasheed songs with the aesthetic and committed accents of western culture. An analytical understanding of this phenomenon is here proposed.